Effect of vacuum mixing and manual pressurisation on residual strains in polymethyl methacrylate bone cement mantles. (20th October 2010) - Hingston, John A.; Looney, Lisa; Dunne, Nicholas J.; McGuinness, Garrett B.
Residual stresses associated with the polymerisation and subsequent cooling of PMMA bone cement are suspected to be responsible for the initiation of cement cracks following total hip arthroplasty (THA). A previous study has measured temperatures and strains developed in a twin cylinder construct representing the implant and femur, during and after bone cement polymerisation, for hand mixed PMMA bone cement. In the present study, the effect of manual pressurisation of the cement mantle is experimentally investigated through stem and femur strain measurements which are directly attributable to cement stresses. Manual pressurisation of the curing cement mass had a significant effect on the measured residual strains. The mean representative femur hoop residual strain was reduced from a compressive strain of -1802 (± 449.8) με to tensile strain of 49 (± 374.3) με, while the mean axial residual strain reduced from -649.2 (± 196.6) με to -271.0 (± 173.6) με. This study demonstrates that a reduction in net residual stress may be achieved by pressurisation of the bone cement mantle.